THE EXISTENCE OF ISLAMIC RELIGIOUS EDUCATION LEARNING IN IMPROVING STUDENTS' RELIGIOUS UNDERSTANDING - Akbar, Amina; Tang, Muhammad; St. Habibah (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
This study aims to answer the focus of the research on the stated research objectives, namely to determine the methods and learning strategies applied by Islamic Religious Education teachers in improving students' religious understanding at SMP Negeri 33 Konawe Selatan. What influences the success of Islamic Religious Education learning in improving students' religious understanding at SMP Negeri 33 Konawe Selatan. The Existence of Islamic Religious Education Learning in Improving Students' Religious Understanding at SMP Negeri 33 Konawe Selatan. In answering the problems in this study, the researcher used qualitative research. With the method of collecting data observation, interviews and documentation. Furthermore, the data obtained were analyzed by data reduction, data presentation, drawing conclusions. using Miles and Huberman Data Types. The results of this study indicate that A. Methods and Learning Strategies Applied by Islamic Religious Education Teachers in Improving Students' Religious Understanding at SMP Negeri 33 Konawe Selatan, namely 1. Lecture Method; 2. Discussion Method; 3. Question and Answer Method. B. What Influences the Success of Islamic Religious Education Learning in Improving Students' Religious Understanding at SMP Negeri 33 Konawe Selatan, namely 1. Quality of Teacher Teaching; 2. Student Motivation and Interest; 3. Curriculum and Teaching Materials; 4. Parental Support. The Existence of Islamic Religious Education Learning in Improving Students' Religious Understanding at SMP Negeri 33 Konawe Selatan, namely 1. Creed Islamic Religious Education learning contributes to strengthening students' creed, deepening their belief in Islamic teachings and strengthening their faith; 2. Worship This learning helps students understand and carry out worship properly, including prayer, fasting, and other religious obligations; 3. Morals Religious education in this school also has an impact on the formation of students' morals, such as honesty, politeness, and social concern in accordance with Islamic teachings